Strengthening Personal Data Protection, Cyber Security, and Improving Public Awareness in Indonesia: Progressive Legal Perspective - Abraham Ethan Martupa Sahat Marune; Brandon Hartanto (International Journal of Business, Economics, and Social Development, 2021)
The development of technology, communication, and the internet has positive and negative influences on all sectors of life in society. One of the negative impacts and problems is the alleged criminal act of buying and selling data and the absence of a special law (lex specialist) regarding the regulation of Indonesian personal data. The purpose of this research is to analyze in-depth the efforts to strengthen the protection of personal data, cyber security, and increase public awareness of the perspective of Progressive Law in Indonesia. This study uses a normative juridical method using secondary data, a statutory approach, a conceptual approach, and a case approach. This scientific paper concludes that the Synergy of Ministries and related institutions (Legislative, Executive, and Judiciary) is the key to protecting personal data and cyber resilience. Then, strengthening efforts should be made, namely immediately passing the Draft Law on Personal Data Protection (RUU PDP), forming an independent institution. However, if at this time a dispute occurs, it can be resolved by Article 30 of the ITE Law and the PMH Lawsuit (Tort), supported by a progressive legal approach and futuristic interpretation by the judge examining the quo case. The synergy of government agencies, the private sector, and other stakeholders is needed to increase public awareness by increasing education/dissemination of efforts to prevent misuse of personal data.